Edukasi Kesehatan tentang Penyakit Tuberkulosis pada Peserta Klub Prolanis BPJS - Asmalinda, Wita; Sapada, Edy (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2024)
Indonesia is the first country among the Hight Burden Countries(HBC) in the WHO South-East Asian region can to active global tuberculosis target for case detection and successful treatment. The type of community service carried out is Community Patnership Program (PKM) in the form of providing education/ counseling to participants of the Ibnu Sina Palembang Clinic’s BPJS Health Prolanis Club at total 20 participants running smoothly. This community service activity was carried out for 2 day ehich was used for educational preparation in the form og arranging a community service permit to Ibnu Sina Clinic prolanis club as a place for carring out community service, preparing the place, traning facilities and tools as wellas food and lunch for partisipans and organizers educational active All 20 participant can take part in the traning completion, namely from 15.00 a.m to 17.00 a.m. It can be concluded that education about Tuberculosisi can increase the knowledge and interest in learning of BPJS Health Club participants regarding Tuberculosis.